2000
DOI: 10.1002/1097-4644(20000901)78:3<429::aid-jcb8>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Potent inhibitory action of red wine polyphenols on human breast cancer cells

Abstract: Breast cancer (one of the most common malignancy in Western societies), as well as esophagus, stomach, lung, bladder, and prostate cancer, depend on environmental factors and diet for growth and evolution. Dietary micronutriments have been proposed as effective inhibitory agents for cancer initiation, progression, and incidence. Among them, polyphenols, present in different foods and beverages, have retained attention in recent years. Red wine is a rich source of polyphenols, and their antioxidant and tumor ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
150
1
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(168 citation statements)
references
References 54 publications
12
150
1
3
Order By: Relevance
“…2). Individual phenol- ic compounds and phenolic extracts of fruit and wine have proven to be very active antiproliferative agents (25,49,50). Hence, the six samples were selected on the basis of given phenolic abundance and diversity among wines (Table 3) in order to study their cytotoxicity eff ects.…”
Section: Cytotoxic Eff Ect Of Selected Fruit Winessupporting
confidence: 93%
“…2). Individual phenol- ic compounds and phenolic extracts of fruit and wine have proven to be very active antiproliferative agents (25,49,50). Hence, the six samples were selected on the basis of given phenolic abundance and diversity among wines (Table 3) in order to study their cytotoxicity eff ects.…”
Section: Cytotoxic Eff Ect Of Selected Fruit Winessupporting
confidence: 93%
“…Many in vitro and animal model studies have shown that resveratrol treatment exhibits anticancer effects. For example, resveratrol treatment can reduce proliferation of several mammalian cancer cell lines (Bhat et al, 2001;Damianaki et al, 2000;Jang et al, 1997) and induce apoptosis in skin, colon, and breast cancer models in vivo (Alirol and Martinou, 2006;Bove et al, 2002;Fremont, 2000;Gusman et al, 2001;Hsieh et al, 1999). Furthermore, many studies have demonstrated that resveratrol can inhibit several events during carcinogenesis (e.g., tumor initiation, promotion and progression) (Bishayee 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol has recently attracted considerable interest because of its inhibitor activity on multiple cellular events associated with carcinogenesis (Jang et al, 1997;Runqing et al, 1999). Resveratrol has been shown to have potent growth inhibitory effects on various cancer cells such as colonic tumor cells (Schneider et al, 2000), leukemic cells (Gautam et al, 2000;Dorrie et al, 2001), breast and prostate cancer cells (Mitchell et al, 1999;Damianaki et al, 2000), and has been suggested as one of the most promising cancer chemopreventive agents.…”
mentioning
confidence: 99%